Planning for Clean Water Needs in ITP Main Building - Sulaeman; Ikhsan Arif (Jurnal Teknik Mesin, 2022)
Plumbing system planning is an important part of a building to meet clean water needs. This study aims to plan a plumbing system for clean water in the ITP main building. Meeting the needs of clean water is planned to use water sources from shallow wells that are pumped into the roof tank (roof tank) and flowed gravitationally to pump two. The results of the calculation of the average water requirements of office buildings are 53 liters / day. The capacity of the roof tank needed to accommodate clean water is 2,100 liters, using two roof tanks with a capacity of 1,050 liters each. Roof tanks are placed on top of towers as high as 7.15 m. The diameter of the clean water pipe needed is 20-50 mm. The pump power needed is 0.071 kw and for the second pump is 0.63 kw. The type of pipe planned for this clean water plambing system is Polyvinyl Chloride (PVC) pipe.